1986
DOI: 10.1136/jcp.39.5.535
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterisation of intestinal spirochaetes.

Abstract: and the *Bacteriology Laboratory, Bradford Royal Infirmary, Bradford SUMMARY Faeces or rectal swabs from 1527 subjects were examined for the presence of intestinal spirochaetes by anaerobic culture on blood agar incorporating spectinomycin (400 mg/l). Twenty three specimens (1-5%) were positive, and only one of these came from a patient with diarrhoea. All positive specimens came from either Asians or known homosexuals. Comparative tests showed a close phenotypic similarity between the human isolates and non-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 29 publications
5
38
1
Order By: Relevance
“…However it must be mentioned that only approximately half of the people residing in each village were sampled, therefore estimates of the colonization rate are based upon individuals sampled rather than the total population. In agreement with previous studies, low rates of colonization were found in urbanized indigenous (9n3 %) and non-indigenous (0 %) individuals [14,26]. A similarity between the current study and the studies conducted in Oman and Australia was the comparatively low rate of colonization amongst children aged 2 years and under.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However it must be mentioned that only approximately half of the people residing in each village were sampled, therefore estimates of the colonization rate are based upon individuals sampled rather than the total population. In agreement with previous studies, low rates of colonization were found in urbanized indigenous (9n3 %) and non-indigenous (0 %) individuals [14,26]. A similarity between the current study and the studies conducted in Oman and Australia was the comparatively low rate of colonization amongst children aged 2 years and under.…”
Section: Discussionsupporting
confidence: 92%
“…Multilocus enzyme electrophoresis has been used to show that human and animal strains of S. pilosicoli were genetically closely related, but did not share the same haplotype [6]. In previous studies, high rates of colonization ( 30 %) with S. pilosicoli have been found in subjects from developing countries [22], disadvantaged indigenous groups [14], AIDS patients [23], and homosexual males [6,24,25], whilst the organisms are rarely isolated from other individuals in Western communities [14,26].…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence rates for B. pilosicoli in the faeces of these populations vary from y10 to 50%. It is rarely identified in other populations [12,15]. B. pilosicoli also colonizes many animal species, and is a well-recognized pathogen of pigs and poultry [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown to colonize approximately 30 % of individuals in developing countries including Oman [8] and Papua New Guinea [9], and, in developed countries, occurs at a similarly high prevalence in Aboriginal people in Australia [10], male homosexuals [3] and patients infected with human immunodeficiency virus (HIV) [11]. By comparison, it is uncommon in the faeces of the general population in developed countries [10,12,13]. It is also regularly found in the large intestines of a variety of animal species including pigs [2], chickens [14], water birds [15], and dogs [16].…”
Section: Introductionmentioning
confidence: 99%